Adapting Pandemic Practices for the Future: Blended Learning Model for Online Advocacy Training in Pakistan. (July 2021) - Awan, Hadia
The challenge of teaching a skill-based course online, during pandemic unfolded lasting/ground-breaking opportunities for teachers and students of law alike. For the advocacy skills' training course, a suit for dissolution of marriage was selected and training was divided into 12 steps. The pre-planned semester calendar of the University was followed, but in the virtual learning environment (VLE), sessions were held mostly synchronously by using an indigenized blended learning (BL) model. Station rotation (SR) and the flipped classroom (FC) were also indigenized for effective use. Indigenization of BL was done. SR was done by creating stations comprising research areas involved in the trial for dissolution of a marriage. The FC was used to make students learn lectures beforehand, and all simulations, role-plays and activities were done in class. On-spot grading was done on assessment rubrics by using standard observation forms, generated based on extracted principles. All rubrics and standard forms were shared and discussed with students to build trust in the VLE. The asynchronous mode was also used, but only for the sake of supplemented learning. The grading policy was revised, and the curves of summative and formative assessments were flattened. A total of 45 students were trained, out of whom 26 scored A, four A–, two B, five B+, one B–, one C, one C+, one C– and four got F (for not participating at all). The outcome was encouraging. After completion of the semester, the need assessment survey culminated in a hands-on training session for the Faculty of Law (FoL). Participants designed courses using the BL model and found the methodology effective for future use in regular classes.